Proses Bernegosiasi Masyarakat Ponorogo Dalam Tradisi Larangan-Larangan Perkawinan Jawa - Miftahul Huda (Al-Risalah, 2017)
This article focuses on negotiating processes that are implemented by five Nadhliyyin-Muhammadiyah families in Ponorogo in seeking of solutions for traditional marriage prohibitions. The processes can be divided into three schematic phases. The first, pre-negotiation process, is based on both personal and collegial conviction between two parts, principles of willingness to seek some creative options, and principles to emphasize bridal candidate’s importances. The second, negotiation process consists some activities such as discussion and debate facing some prohibitions in Javanese marriage. The last process, post-negotiation, is the result of negotiation process that can be distinguished into two things: agreement or similar view that enable the marriage to continue and difference that divorce the spouse.